2008
DOI: 10.1071/ar08104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci associated with salt tolerance during seedling growth in soybean (Glycine max L.)

Abstract: Salt stress is an important factor affecting the growth and development of soybean. The inheritance and expression of traits associated with salt tolerance during the seedling stage are complex. The present study was conducted to identify quantitative trait loci (QTLs) associated with salt tolerance during seedling growth in soybean. Field and greenhouse experiments were conducted to evaluate 184 recombinant inbred lines (RILs) derived from a cross between Kefeng No. 1 and Nannong1138-2 for salt tolerance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 27 publications
1
49
0
1
Order By: Relevance
“…SSR marker Satt255 is null in the S-100 and Lee soybean cultivars investigate the performance of the QTL effect of interest in different genetic backgrounds. Comparison of salt tolerance performance of the three sets of NILs showed that the sensitive line of NILs25 had a higher salt tolerance than that of the NILs18 and NILs72, suggesting that there might be another gene that affects or interacts with the salt tolerance gene in linkage group N. Chen et al (2008) detected salttolerant QTLs in several linkage groups, such as linkage groups G, M, and K. In addition, Lee et al (2009) reported a new salt tolerant gene, which is different from the gene in S-100. However, they did not identify the genomic position of the new salt tolerant gene.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…SSR marker Satt255 is null in the S-100 and Lee soybean cultivars investigate the performance of the QTL effect of interest in different genetic backgrounds. Comparison of salt tolerance performance of the three sets of NILs showed that the sensitive line of NILs25 had a higher salt tolerance than that of the NILs18 and NILs72, suggesting that there might be another gene that affects or interacts with the salt tolerance gene in linkage group N. Chen et al (2008) detected salttolerant QTLs in several linkage groups, such as linkage groups G, M, and K. In addition, Lee et al (2009) reported a new salt tolerant gene, which is different from the gene in S-100. However, they did not identify the genomic position of the new salt tolerant gene.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, they also indicated that the salt tolerance confers a large dominant effect over salt sensitivity. Chen et al (2008) evaluated the salt tolerance of 184 F 7:11 RILs derived from a cross between a salttolerant soybean cultivar Kefeng No. 1 and a saltsensitive soybean cultivar Nannong1138-2.…”
Section: Introductionmentioning
confidence: 99%
“…Several independent studies consistently verified a major quantitative trait locus (QTL) on Chromosome 3 for soybean tolerance to NaCl stress (Chen et al, 2008; Hamwieh and Xu, 2008; Hamwieh et al, 2011; Ha et al, 2013). A cation/H + exchanger family gene, GmCHX1/GmSALT3/Ncl/ ( Glyma03g32900 ), was identified in this genomic region, which regulated Na + , K + , and Cl - homeostasis in the shoot of soybean under NaCl stress, and the functional allele of this gene could improve soybean salt tolerance and yield under salinity stress (Guan et al, 2014; Qi et al, 2014; Tuyen et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…QTLs conditioning salt tolerance in soybean have been identified using recombinant inbred lines (RIL) derived from crosses between salt-tolerant and -susceptible genotypes, (Lee et al, 2004;Chen et al, 2008;Hamwieh and Xu, 2008;Hamwieh et al, 2011;Xu and Tuyen, 2012). A gene conditioning supernodulation has been identified (Arai et al, 2005;Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%